(untitled) (International relations and international law Journal, 2018)
The process of economic globalization, covering virtually all spheres of human activity, significantly expanded the world economic ties in the 21st century, which in turn led to the formation of a more complex structure of the international labor market, a change in the regulation of the labor market, and the emergence of new trends in international labor migration. The purpose of the article is to examine theoretical aspects in labor market research in conjunction with international labor migration. In the scientific works of Western authors, the evolution of such a process is studied, as a result of which the national labor markets of most leading countries are no longer isolated structures, they have long been integrated, and moreover, they are associated with the dynamics of the movement of labor force. Transnational migration of labor resources has now acquired a regular, sustainable character. The study of the destination of migrants, the definition of the peculiarities of labor migration indicates a lack of theoretical comprehension of the studied processes in the regional section. The theoretical significance of the work lies in the deepening and development of the methodology for studying the world and national labor markets in the context of globalization and technological transformation, which in turn facilitates the harmonization of different scientific approaches and overcoming the fragmented nature of scientific knowledge in this important scientific field. In practical terms, the study of this topic will allow us to use the main findings in further scientific research and analysis of the current development of the world and national labor market, to identify key areas in the development of international labor migration. Key words: labor, migration, evolution, international, history.